3DCRTversus RapidArc treatment for breast cancer:dosimetric study - Tolba, Aida. R.; Allehyani, Saud. H.; Sharyan, Huda. A.; Ibrahim, H. S. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The Aim of this study is to compare (3D-CRT) to RapidArc planning systems using (LNAC of 6 MV, 15 MV and 18 MV) in terms of dosimetric outcomes of iso-dose distribution, dose volume histogram (DVH), PTV and at risk organs in 6 patients with breast cancer. The mean value of the PTV was (51.38 ± 2.172) in RapidArc compared to(52.21 ± 1.963) in 3D-CRT , which means that RapidArc plan achieved lower mean and maximum doses to the PTV.. RapidArc plan showed a more homogeneous dose distribution in PTV, achieving an HI of 1.262 ± 0.037 compared with 1.271 ± 0.024 in the 3D-CRT plan however, RapidArc and 3D-CRT achieved similar CI values and improvement in target coverage index (TCI) in which (TCI) in RapidArc was (0.006 ± 0.003) and (0.008 ± 0.006) in 3D-CRT, (P = 0.202). Volumetric modulated arc therapy (VMAT) is better than 3D-CRT in term of PTV, conformity and homogeneity for breast cancer.